The relationship between fears of cancer recurrence and patient age: A systematic review and meta‐analysis. Issue 3 (20th February 2020) - Lim, Edward; Humphris, Gerald
Abstract: Background: Fears of cancer recurrence (FCR) is one of the most prevalent concerns and a common unmet need reported by cancer patients. Patient age is a demographic variable that has been linked to FCR, among others. Although it is recognised by researchers that age and FCR may be negatively correlated, the strength of this correlation has yet to be established. Aim: The aims of this study were to (a) conduct a meta‐analysis to investigate the overall association of patient age in years with FCR across studies from 2009 to February 2019 and (b) scrutinise for patterns of these effect sizes across studies. Methods and Results: Peer‐reviewed papers were gathered from the literature via online databases (PubMed, EMBASE, MEDLINE, and PsycINFO). Systematic review guidelines including a quality assessment were applied to the 31 selected studies (pooled participant N size = 19 777). The meta‐analysis demonstrated a significant negative association between age and FCR (ES = −0.12; 95% CI, −0.17, −0.07). Meta‐regression revealed the association of patient age and FCR significantly reduced over the last decade. A significant effect ( β = −0.17, P = 0.005) of breast cancer versus other cancers on this age by FCR association was also identified. Conclusion: The reliable and readily accessible personal information of age of patient can be utilised as a weak indicator of FCR level especially in the breast cancer field, where the majority of studies were drawn. The suggestion that age and FCR association may be attenuated in recent years requires confirmation.